Zn-Fe Double Hydroxide-Carbon Nanotube Anodes for Asymmetric Supercapacitors - Liang, Wenyu; Zhitomirsky, Igor (Frontiers in Materials, 2020)
Zn-Fe double hydroxide (Zn-Fe-DH) – multiwalled carbon nanotube (MWCNT) composite has been developed as a new material for energy storage in negative electrodes of asymmetric supercapacitors. A conceptually new approach is based on the use of celestine blue (CB) dye as a multifunctional additive. We discovered that CB acted as a co-dispersant for Zn-Fe-DH and MWCNT and facilitated their mixing. New strategy was based on the use of CB as charge transfer mediator, which facilitated charge-discharge reactions. The electrodes showed a capacitance of 5.2 F cm–2 in 0.5 M Na2SO4 electrolyte in a voltage window of −1.0 to −0.2 V vs. saturated calomel electrode and good cyclic stability. A new asymmetric device has been developed, containing Zn-Fe-DH-MWCNT negative electrodes and polypyrrole coated MWCNT positive electrodes. Good capacitive behavior of cathode and anode materials was achieved at high active mass of 40 mg cm–2 in partially overlapping potential windows. The device showed promising performance in a voltage window of 1.6 V. The capacitance of 2.2 F cm–2 was obtained at a scan rate of 2 mV s–1.